Cutting Sugar Cane, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
A picture of labourers in the cane field cutting while a man in a pith helmet stands next to a laden cart.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Sugarcane industry--Trinidad and Tobago; Sugarcane--Trinidad and Tobago; Working class--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Plantation overseers--Trinidad and Tobago; 1928